Microbial Community Response to Terrestrially Derived Dissolved Organic Matter in the Coastal Arctic - Sipler, Rachel E.; Kellogg, Colleen T. E.; Connelly, Tara L.; Roberts, Quinn N.; Yager, Patricia L.; Bronk, Deborah A. (Frontiers in Microbiology, 2017)
Warming at nearly twice the global rate, higher than average air temperatures are the new ‘normal’ for Arctic ecosystems. This rise in temperature has triggered hydrological and geochemical changes that increasingly release carbon-rich water into the coastal ocean via increased riverine discharge, coastal erosion, and the thawing of the semi-permanent permafrost ubiquitous in the region. To determine the biogeochemical impacts of terrestrially-derived dissolved organic matter (tDOM) on marine ecosystems we compared the nutrient stocks and bacterial communities present under ice-covered and ice-free conditions, assessed the lability of Arctic tDOM to coastal microbial communities from the Chukchi Sea, and identified bacterial taxa that respond to rapid increases in tDOM. Once thought to be predominantly refractory, we found that 7% of dissolved organic carbon and 38% of dissolved organic nitrogen from tDOM was bioavailable to receiving marine microbial communities on short 4 - 6 day time scales. The addition of tDOM shifted bacterial community structure toward more copiotrophic taxa and away from more oligotrophic taxa. Although no single order was found to respond universally (positively or negatively) to the tDOM addition, this study identified 20 indicator species as possible sentinels for increased tDOM. These data suggest the true ecological impact of tDOM will be widespread across many bacterial taxa and that shifts in coastal microbial community composition should be anticipated.